(untitled) (Global Journal of Human-Social Science, 2023)
Colors are a world of magic and beauty and a dazzling luster that gives things beauty and splendor Colors play an important role in our lives as they cause us joy and adornment and without colors life becomes bleak and boring Colors affect human souls their tendencies desires preparations psychological and physical state and these effects reach the depths of the human psyche and are divided into positive effects that express comfort love and joy and negative effects that arouse feelings of anxiety turmoil and sadness in our souls Thus the aim of the study is to provide a design which helps changing the internal environment of the places with the respect of the occupant s moods